The poetics of palliation : romantic literary therapy, 1790-1850 - Pladek, Brittany (Romantic reconfigurations., 2019)
The Poetics of Palliation argues that Romanticism developed richer literary therapies than its contemporary reception remembers. By reading Romantic writers against Georgian medical ethics, Poetics recovers their models of literature as comfort and sustenance, challenging a health humanities tradition that sees literary therapy primarily as cure.